Carprofen elicits pleiotropic mechanisms of bactericidal action with the potential to reverse antimicrobial drug resistance in tuberculosis. (13th August 2020) - Maitra, Arundhati; Evangelopoulos, Dimitrios; Chrzastek, Alina; Martin, Liam T; Hanrath, Aidan; Chapman, Ellie; Hailes, Helen C; Lipman, Marc; McHugh, Timothy D; Waddell, Simon J; Bhakta, Sanjib
Abstract: Background: The rise of antimicrobial drug resistance in Mycobacterium tuberculosis coupled with the shortage of new antibiotics has elevated TB to a major global health priority. Repurposing drugs developed or used for other conditions has gained special attention in the current scenario of accelerated drug development for several global infectious diseases. In a similar effort, previous studies revealed that carprofen, a non-steroidal anti-inflammatory drug, selectively inhibited the growth of replicating, non-replicating and MDR clinical isolates of M. tuberculosis . Objectives: We aimed to reveal the whole-cell phenotypic and transcriptomic effects of carprofen in mycobacteria. Methods: Integrative molecular and microbiological approaches such as resazurin microtitre plate assay, high-throughput spot-culture growth inhibition assay, whole-cell efflux inhibition, biofilm inhibition and microarray analyses were performed. Analogues of carprofen were also synthesized and assessed for their antimycobacterial activity. Results: Carprofen was found to be a bactericidal drug that inhibited mycobacterial drug efflux mechanisms. It also restricted mycobacterial biofilm growth. Transcriptome profiling revealed that carprofen likely acts by targeting respiration through the disruption of membrane potential. The pleiotropic nature of carprofen's anti-TB action may explain why spontaneous drug-resistant mutants could not be isolated in practice. Conclusions: This immunomodulatory drug and its chemical analogues have the potential to reverse TB antimicrobial drug resistance, offering a swift path to clinical trials of novel TB drug combinations.